Bela Negara Dalam Perspektif Al- Qur’an (Tinjauan Analisis Teori Dan Praktik) - Suhaidi (Universitas Garut, 2025)
The issue of national defense in Islam in Indonesia is indeed quite complex. National defense is not only a geographical issue, but also a matter of local and cultural values ​​that should serve as a bridge between Islamic values ​​and statehood.